Glypican-3-Targeted Alpha Particle Therapy for Hepatocellular Carcinoma - Meghan M. Bell; Nicholas T. Gutsche; A. Paden King; Kwamena E. Baidoo; Olivia J. Kelada; Peter L. Choyke; Freddy E. Escorcia (Molecules, 2020)
Glypican-3 (GPC3) is expressed in 75% of hepatocellular carcinoma (HCC), but not normal liver, making it a promising HCC therapeutic target. GC33 is a full-length humanized monoclonal IgG1 specific to GPC3 that can localize to HCC in vivo. GC33 alone failed to demonstrate therapeutic efficacy when evaluated in patients with HCC; however, we posit that cytotoxic functionalization of the antibody with therapeutic radionuclides, may be warranted. Alpha particles, which are emitted by radioisotopes such as Actinium-225 (Ac-225) exhibit high linear energy transfer and short pathlength that, when targeted to tumors, can effectively kill cancer and limit bystander cytotoxicity. Macropa, an 18-member heterocyclic crown ether, can stably chelate Ac-225 at room temperature. Here, we synthesized and evaluated the efficacy of [225Ac]Ac–Macropa–GC33 in mice engrafted with the GPC3-expressing human liver cancer cell line HepG2. Following a pilot dose-finding study, mice (n = 10 per group) were treated with (1) PBS, (2) mass-equivalent unmodified GC33, (3) 18.5 kBq [225Ac]Ac–Macropa–IgG1 (isotype control), (4) 9.25 kBq [225Ac]Ac–Macropa–GC33, and (5) 18.5 kBq [225Ac]Ac–Macropa–GC33. While significant toxicity was observed in all groups receiving radioconjugates, the 9.25 kBq [225Ac]Ac–Macropa–GC33 group demonstrated a modest survival advantage compared to PBS (p = 0.0012) and 18.5 kBq [225Ac]Ac–IgG1 (p = 0.0412). Hematological analysis demonstrated a marked, rapid reduction in white blood cells in all radioconjugate-treated groups compared to the PBS and unmodified GC33 control groups. Our studies highlight a significant disadvantage of using directly-labeled biomolecules with long blood circulation times for TAT. Strategies to mitigate such treatment toxicity include dose fractionation, pretargeting, and using smaller targeting ligands.